Brief Episodes of Nocturnal Hypoxia and Acidification Reduce Survival of Economically Important Blue Crab (Callinectes sapidus) Larvae - Tomasetti, Stephen J.; Kraemer, Jeffrey R.; Gobler, Christopher J. (Frontiers in Marine Science, 2021)
Many shallow coastal systems experience diel fluctuations in dissolved oxygen (DO) and pH that can intensify throughout the summer season and expose estuarine organisms to repeated episodes of coastal hypoxia and acidification. In temperate regions, larval release of the economically important blue crab Callinectes sapidus occurs in the summer, and while the earliest stage (zoea I) larvae are susceptible to persistent low DO and low pH conditions, their sensitivity to diel fluctuations is unknown. Here, a series of short-term (≤96 h) experiments were conducted to investigate the survival of C. sapidus zoea I larvae exposed to a range of diel cycling hypoxic and acidified conditions and durations. Two experiments comparing a diel cycling DO/pH treatment (fluctuating from ~30% air saturation to ~103% averaging ~66% / and from pH ~7.26 to ~7.80 averaging ~7.53) to a static low DO/pH treatment (~43% / ~7.35), a static moderate DO/pH treatment (~68% / ~7.59), and a static control treatment (~106% / ~7.94) indicated that survival in the diel cycling treatment was significantly lower than the moderate treatment (p<0.05) by 75% and 48% over 96 h and 48 h respectively, despite comparable mean experimental DO/pH values. Three other experiments aimed at identifying the effective minimum duration of low DO/low pH to significantly depress larval survival under diel cycling conditions revealed that 8 h of low DO/low pH (~28% / ~7.43) over a 24-h diel cycle consistently decreased survival (p<0.05) relative to control conditions by at least 55% regardless of experimental duration (72-h, 48-h, and 24-h experiments). An increase in DO beyond saturation to supersaturation (160%) and pH beyond normocapnic to highly basified (8.34) conditions during the day phase of the diel cycle did not improve survival of larvae exposed to nocturnal hypoxia and acidification. Collectively, these experiments demonstrate that diel cycling does not provide newly hatched C. sapidus larvae a temporal refuge capable of ameliorating low DO/pH stress, but rather is more lethal than chronic exposure to comparable average DO/pH conditions. Given that larvae exposed to a single nocturnal episode of moderate hypoxia and acidification experience significantly reduced survival, such occurrences may depress larval recruitment.